2015
DOI: 10.1039/c4cc08367a
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide synthesis through copper-catalyzed C–S bond formation under biomolecule-compatible conditions

Abstract: We report here an efficient and mild method for constructing C-S bonds. The reactions were carried out with Na2S2O3 as a sulfurating reagent, CuSO4 as a catalyst, and water as solvent without any surfactant. The products were achieved in moderate to excellent yields at room temperature under air. Notably, this reaction is compatible with various biomolecules including amino acids, oligosaccharides, nucleosides, proteins, and cell lysates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…In contrast with organic thiols and thiophenols, its intrinsic properties helped us to accomplish this S atom transfer reaction in a highly efficient manner. Further study indicated that this transformation could take place between 1-aryltriazenes, Na 2 S 2 O 3 and alkyl halides at room temperature, in which water functioned as a green solvent [32] (Fig. 20b).…”
Section: Synthesis Of Thioethersmentioning
confidence: 99%
“…In contrast with organic thiols and thiophenols, its intrinsic properties helped us to accomplish this S atom transfer reaction in a highly efficient manner. Further study indicated that this transformation could take place between 1-aryltriazenes, Na 2 S 2 O 3 and alkyl halides at room temperature, in which water functioned as a green solvent [32] (Fig. 20b).…”
Section: Synthesis Of Thioethersmentioning
confidence: 99%
“…The same author later reported milder conditions for the synthesis of aryl sulfides by using CuSO 4 in pure water as solvent. 76 Instead of diazo compounds generated from anilines, 1-aryltriazenes serve as the aromatic partner. Again, Na 2 S 2 O 3 is used as the source of the sulfur atom (eq 49).…”
Section: Martin Pichette Drapeau and Thierry Ollevier Université Lavalmentioning
confidence: 99%
“…An efficient and green approach for the synthesis of aryl alkyl sulfides from the reaction of 1-aryltriazenes with alkyl halides and Na 2 S 2 O 3 was reported using CuSO 4 as the catalyst in aqueous media (Scheme 73). 82 Only poor yields were obtained in the absence of the catalyst and ligand. The presence of BF 3 .OEt 2 was crucial for the reaction to proceed.…”
Section: Thiourea As the Sulfur Sourcementioning
confidence: 98%